Solar urticaria: clinical characteristics, treatment effectiveness, long-term prognosis, and QOL status in 29 patients - Imamura, Shinya; Oda, Yoshiko; Fukumoto, Takeshi; Mizuno, Mayuko; Suzuki, Mariko; Washio, Ken; Nishigori, Chikako; Fukunaga, Atsushi (Frontiers in Medicine, 2024)
Abstract Introduction: Solar urticaria (SU), a relatively rare skin inflammatory and photosensitivity disease, is often resistant to standard urticaria treatment. Quality of life (QOL) among SU patients has not been extensively explored. This study was performed to clarify the clinical features and effectiveness of therapies (e.g., hardening therapy) for SU and to determine QOL among SU patients. Methods: We examined the characteristics, treatments, and QOL statuses of 29 Japanese SU patients using medical records and a questionnaire approach. Results: Among 29 patients, H1 antihistamine therapy (H1) was effective in 22 (75.8%). H2 antihistamine therapy (H2) was effective in three of seven patients (42.9%). UVA hardening therapy was effective in eight of nine patients (88.9%). Visible light (VL) hardening therapy was ineffective in three of three patients. In one patient who underwent both UVA and VL hardening therapy, only UVA hardening therapy was effective. In the questionnaire, 18 patients (90%) reported some improvement compared with disease onset (four had complete remission, six had completed treatment although mild symptoms persisted, and eight were receiving treatment with moderate symptoms), whereas two patients reported exacerbation. Patients in complete remission had a mean disease duration of 4 years, whereas patients not in remission had a mean disease duration of 8.8 years. The mean Dermatology Life Quality Index (DLQI) score for the current status was 7.4. There was a correlation between DLQI and symptom/treatment status. However, neither DLQI and action spectra nor DLQI and treatments exhibited significant differences. Discussion: The questionnaire revealed current QOL status and long-term prognosis in SU patients. Compared with disease onset, most patients exhibited improvement when assessed for this study. Both H1 and H2 should be attempted for all SU patients. UVA hardening therapy may be an option for SU patients with an action spectrum that includes UVA.